An appraisal of the contribution of the barrio schools of Tuguegarao, Cagayan to community development (1972-1974) - Montero, Herminia Diego 1929- (1975)
Twenty barrio school heads and 200 teachers and parents indicated that the barrio schools contributed most in 1972-1974 in the areas of (1) Health and Sanitation in the upkeep of yards and surroundings; (2) Literacy; (3) Citizenship and cultural development by organizing literary-musical and social activites; and (4) Economic growth by promoting the Green Revolution. The most effective approaches to community development include using the school as a model of beauty, cleanliness, sanitation and stepped-up food production; visitation of teachers to pupils' homes especially when their pupils are sick; supervising the home projects of pupils; building sanitary toilets and providing receptacles for trash in public centers; and teacher modelling.
Thesis (M.Ed.)--University of the Philippines
Keywords: Rural schools -- Philippines -- Tuguegarao; Community and school; Community development -- Tuguegarao